Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To find [tex]\(h'(-1)\)[/tex] where [tex]\(h(x) = \frac{3}{[g(x)]^4}\)[/tex], let's follow these steps:
1. Express [tex]\(h(x)\)[/tex] explicitly:
[tex]\[ h(x) = 3 [g(x)]^{-4} \][/tex]
2. Compute the derivative [tex]\(h'(x)\)[/tex] using the chain rule:
[tex]\[ h(x) = 3 [g(x)]^{-4} \][/tex]
Let [tex]\(u = g(x)\)[/tex]. Then [tex]\(h(x) = 3 u^{-4}\)[/tex].
Compute the derivative [tex]\(\frac{d}{dx}[3 u^{-4}]\)[/tex]:
[tex]\[ \frac{d}{dx}[3 u^{-4}] = 3 \cdot (-4) u^{-5} \frac{du}{dx} \][/tex]
[tex]\[ \frac{d}{dx}[3 u^{-4}] = -12 u^{-5} \frac{du}{dx} \][/tex]
3. Substitute back [tex]\(u = g(x)\)[/tex] and the chain rule result:
[tex]\[ h'(x) = -12 [g(x)]^{-5} g'(x) \][/tex]
4. Evaluate [tex]\(h'(-1)\)[/tex] using the given values from the table:
From the table:
[tex]\[ g(-1) = 6 \][/tex]
[tex]\[ g'(-1) = 1 \][/tex]
Substitute [tex]\(g(-1)\)[/tex] and [tex]\(g'(-1)\)[/tex] into the derivative formula:
[tex]\[ h'(-1) = -12 [g(-1)]^{-5} g'(-1) \][/tex]
5. Calculate [tex]\(h'(-1)\)[/tex]:
[tex]\[ h'(-1) = -12 [6]^{-5} \cdot 1 \][/tex]
[tex]\[ h'(-1) = -12 \cdot 6^{-5} \cdot 1 \][/tex]
6. Simplify [tex]\(6^{-5}\)[/tex]:
[tex]\[ 6^{-5} = \frac{1}{6^5} = \frac{1}{7776} \][/tex]
[tex]\[ h'(-1) = -12 \cdot \frac{1}{7776} \][/tex]
[tex]\[ h'(-1) = -\frac{12}{7776} = -\frac{1}{648} \approx -0.001543 \][/tex]
7. Round the answer to 3 decimal places:
[tex]\[ h'(-1) \approx -0.002 \][/tex]
So, the value of [tex]\(h'(-1)\)[/tex] is [tex]\(-0.002\)[/tex].
1. Express [tex]\(h(x)\)[/tex] explicitly:
[tex]\[ h(x) = 3 [g(x)]^{-4} \][/tex]
2. Compute the derivative [tex]\(h'(x)\)[/tex] using the chain rule:
[tex]\[ h(x) = 3 [g(x)]^{-4} \][/tex]
Let [tex]\(u = g(x)\)[/tex]. Then [tex]\(h(x) = 3 u^{-4}\)[/tex].
Compute the derivative [tex]\(\frac{d}{dx}[3 u^{-4}]\)[/tex]:
[tex]\[ \frac{d}{dx}[3 u^{-4}] = 3 \cdot (-4) u^{-5} \frac{du}{dx} \][/tex]
[tex]\[ \frac{d}{dx}[3 u^{-4}] = -12 u^{-5} \frac{du}{dx} \][/tex]
3. Substitute back [tex]\(u = g(x)\)[/tex] and the chain rule result:
[tex]\[ h'(x) = -12 [g(x)]^{-5} g'(x) \][/tex]
4. Evaluate [tex]\(h'(-1)\)[/tex] using the given values from the table:
From the table:
[tex]\[ g(-1) = 6 \][/tex]
[tex]\[ g'(-1) = 1 \][/tex]
Substitute [tex]\(g(-1)\)[/tex] and [tex]\(g'(-1)\)[/tex] into the derivative formula:
[tex]\[ h'(-1) = -12 [g(-1)]^{-5} g'(-1) \][/tex]
5. Calculate [tex]\(h'(-1)\)[/tex]:
[tex]\[ h'(-1) = -12 [6]^{-5} \cdot 1 \][/tex]
[tex]\[ h'(-1) = -12 \cdot 6^{-5} \cdot 1 \][/tex]
6. Simplify [tex]\(6^{-5}\)[/tex]:
[tex]\[ 6^{-5} = \frac{1}{6^5} = \frac{1}{7776} \][/tex]
[tex]\[ h'(-1) = -12 \cdot \frac{1}{7776} \][/tex]
[tex]\[ h'(-1) = -\frac{12}{7776} = -\frac{1}{648} \approx -0.001543 \][/tex]
7. Round the answer to 3 decimal places:
[tex]\[ h'(-1) \approx -0.002 \][/tex]
So, the value of [tex]\(h'(-1)\)[/tex] is [tex]\(-0.002\)[/tex].
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.